2017
DOI: 10.1371/journal.pone.0189641
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic markers for the detection of ovarian cancer in BRCA1 mutation carriers

Abstract: BackgroundScreening for ovarian cancer (OC) in women at high risk consists of a combination of carbohydrate antigen 125 (CA125) and transvaginal ultrasound, despite their low sensitivity and specificity. This could be improved by the combination of several biomarkers, which has been shown in average risk patients but has not been investigated until now in female BRCA mutation carriers.MethodsUsing a multiplex, bead-based, immunoassay system, we analyzed the concentrations of leptin, prolactin, osteopontin, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Prolactin was part of a six protein panel of proteins used for early detection of ovarian cancer called Ovasure [20], demonstrating that it is specifically increased in tumorigenesis. Recently, PRL was retested along with seven other proteins and found to be an efficient diagnostic marker for screening OVCA with BRCA1 mutation [37]. However, the presence of PRL in the serum does not address if this is a biomarker of cancer or a driver of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin was part of a six protein panel of proteins used for early detection of ovarian cancer called Ovasure [20], demonstrating that it is specifically increased in tumorigenesis. Recently, PRL was retested along with seven other proteins and found to be an efficient diagnostic marker for screening OVCA with BRCA1 mutation [37]. However, the presence of PRL in the serum does not address if this is a biomarker of cancer or a driver of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The Luminex ® /xMAP ® technology is a bead-based immunoassay that allows for multiplex detection of up to 100 analytes simultaneously [ 41 ]. The commercially available bead panel—applied in [ 29 , 42 , 43 , 44 , 45 ] and our research [ 34 , 35 , 36 ]—offers a wide spectrum of pre-defined biomarkers. Selection and validation of the best performing marker panels is essential for their reasonable and cost-effective use.…”
Section: Discussionmentioning
confidence: 99%
“…In a study including patients with BRCA1 mutation, we observed an excellent performance of the six-protein panel (modified by replacing IGF-2 with HE4) both in OC patients with BRCA1 mutation (AUC 0.98) and wildtype (AUC 0.99). Of particular interest was that the test enabled differentiation between healthy BRCA1 mutation carriers and healthy wildtype women (with 0.88 sensitivity, 0.81 specificity and AUC 0.9) [ 35 ]. Lastly, we re-estimated the six-protein panel and calculated the Proteomic Model 2017, which consisted of CA125, HE4, PRL, OPN and leptin, and reached an AUC of 0.96 in the training cohort [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…MIF has been implicated in the angiogenic switch during progression of early cancers and plays a role in macrophage-induced ovarian cancer cell invasiveness [41,42]. Furthermore, Serum levels of MIF have been used as part of algorithms to detect disease in women with BRCA1/2 mutations and for distinguishing malignant from benign disease [43].…”
Section: Discussionmentioning
confidence: 99%